Long-term follow-up of nutritional status in children with GLUT1 Deficiency Syndrome treated with classic ketogenic diet: a 5-year prospective study - De Amicis, Ramona; Leone, Alessandro; Pellizzari, Marta; Foppiani, Andrea; Battezzati, Alberto; Lessa, Chiara; Tagliabue, Anna; Ferraris, Cinzia; De Giorgis, Valentina; Olivotto, Sara; Previtali, Roberto; Veggiotti, Pierangelo; et al. (Frontiers in Nutrition, 2023)
Introduction The classic ketogenic diet (cKD) is an isocaloric, high fat, low-carbohydrate diet that induces the production of ketone bodies. High consumption of dietary fatty acids, particularly long-chain saturated fatty acids, could impair nutritional status and increase cardiovascular risk. The purpose of this study was to evaluate the long-term effects of a 5-year cKD on body composition, resting energy expenditure, and biochemical parameters in children affected by Glucose Transporter 1 Deficiency Syndrome (GLUT1DS). Methods This was a prospective, multicenter, 5-year longitudinal study of children with GLUT1DS treated with a cKD. The primary outcome was to assess the change in nutritional status compared with pre-intervention, considering anthropometric measurements, body composition, resting energy expenditure, and biochemical parameters such as glucose and lipid profiles, liver enzymes, uric acid, creatinine, and ketonemia. Assessments were conducted at pre-intervention and every 12 months of cKD interventions. Results Ketone bodies increased significantly in children and adolescents, and remained stable at 5 years, depending on the diet. No significant differences were reported in anthropometric and body composition standards, as well as in resting energy expenditure and biochemical parameters. Bone mineral density increased significantly over time according to increasing age. Body fat percentage significantly and gradually decreased in line with the increase in body weight and the consequent growth in lean mass. As expected, we observed a negative trend in respiratory quotient, while fasting insulin and insulin resistance were found to decrease significantly after cKD initiation. Conclusion Long-term adherence to cKD showed a good safety profile on anthropometric measurements, body composition, resting energy expenditure, and biochemical parameters, and we found no evidence of potential adverse effects on the nutritional status of children and adolescents.